ASEAN’s Leadership Capacity as the Heart of the Indo-Pacific - Eva Ermylina; Syasya Yuania Fadila Mas'udi (UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAWA TIMUR, 2026)
Amid intensifying great power competition, the Indo-Pacific concept has emerged as a crucial geopolitical framework that expands traditional constructs of the Asia-Pacific. As major powers such as the United States, Japan, India, and Australia develop Indo-Pacific strategies to counter China's growing influence, the Association of Southeast Asian Nations (ASEAN) seeks to maintain regional stability and relevance through the ASEAN Outlook on the Indo-Pacific (AOIP). Based on the principle of ASEAN Centrality, the AOIP reflects ASEAN's commitment to an inclusive and rules-based regional order and its ambition to be a key architect of Indo-Pacific cooperation. This paper examines ASEAN's leadership using the leadership-institution model, which distinguishes between ideational leadership—grounded in ideas, norms, and identity building—and executive leadership—rooted in material capabilities and institutional authority. The findings highlight ASEAN's strong ideational leadership through its ability to uphold shared principles and facilitate dialogue among diverse actors, despite lacking binding enforcement authority. However, ASEAN's executive leadership remains hampered by weak collective military capacity, economic disparities among member states, and consensus-based decision-making, which often results in non-binding outcomes. Overall, this study demonstrates that while ASEAN plays a crucial role in promoting inclusivity and sustaining dialogue, significant challenges remain in translating its centrality into decisive institutional leadership within the evolving Indo-Pacific architecture.